“Go to Work on Monday One More Time”: An analysis of the compensation process for occupational disease at General Electric in Peterborough - Natasha Luckhardt (My University, 2014)
This paper provides a historical, socioeconomic and political analysis of the compensation claims process for former General Electric workers in Peterborough. To provide context to the issue, the literature analyzes the evolution of the compensation process, the history of asbestos and occupational cancer in Canada and more specifically, Ontario, chemical causation considerations and the government and large industry’s participation in these issues. In order to examine the complexity of the compensation process in Peterborough, the key players involved in the process were interviewed and include representatives from CAW/Unifor, Occupational Health Clinic for Ontario Workers (OHCOW), OWA (Office of the Worker Advisor), Workplace Safety and Insurance Board (WSIB), Occupational and Environmental Health Coalition of Peterborough (O&EHC-P), as well as former workers and their families. The testimonials deliver insight on issues such as the range of asbestos and chemicals used in the plant, the lack of causation data to support workers’ claims, the use and abuse of science in the process, the socioeconomic relevancy of GE in Peterborough, the environmental devastation created by the manufacturing industry in the city and the tensions between the intended and applied responsibilities of the key players. The overall findings were that the workers feel invisible to the major players involved, ignored by the community and overwhelmed by the system. To provide a deeper understanding of these issues, there are three groups of case studies examined: the compensated, the uncompensated and the families. The recommendations include a need for a concerted effort by all key players to ensure the workers’ right to a fair and just compensation process, enhanced education within the community on occupational health and safety, legislation reform, increased causation data, community mobilization efforts and environmental studies examining the water, air and soil in Peterborough and surrounding areas.